A residência multiprofissional em hospital assistencial - Campos Neta, Ana Maria Pedroso De [UNIFESP] (2019)
Based on loco regional and socio epidemiological needs, Multiprofessional Residency Programs in Health are based on principles and guidelines for Brazilian Unified Health System (SUS) which are: National Education Management Policy in Health; expanded health concept; teaching-service-community integration; learning that follows lines of care, integral and interdisciplinary formation; decentralization and regionalization; and articulation with medical residency. In order to improve work processes and favor patient care, Assistance Hospitals could be considered as place of Health System reorganization. OBJECTIVE: This study analyzed Multiprofessional Residency in Health within the context of Municipal Assistance Hospitals of São Paulo and assimilated managers, local coordinators and preceptor perceptions specifically; has mapped potentialities and weaknesses; as well as has presented suggestions for enhancing programs. METHODOLOGY: A qualitative, cross-sectional, exploratory and descriptive approach was adopted. The research was carried out in three Public Assistance Hospitals in São Paulo and, as part of its elaboration, was attended by six managers, three local coordinators and eight preceptors, in a total of 17 participants. The programs analyzed were intensivism, with seven professional areas, as well as those of emergency, with six professional areas. A semi-structured interview was used to collect data. Content analysis was used in the thematic modality and it was based on four thematic nuclei: The role of MRH in Assistance Hospital; potentialities and weaknesses in the programs; and suggestions for enhancing MRH. RESULTS AND DISCUSSION: Following categories emerged regarding the role of Multiprofessional Residency in Health in Assistance Hospitals: MRH as an important landmark for Assistance Hospital; as a tool for transforming Assistance Hospital into Teaching Hospital; as a mechanism of institutional change; as a strategy for continuing and permanent education, which provides shared learning; and as an instrument for enhancing health care. It could be highlighted the following MRH potentialities and weaknesses. As potentialities: implementation of a teaching-learning environment in Assistance Hospitals, stimulation of a greater Care systematization and improvement of clinical staff. As weaknesses: no structured hospital organization for this type of teaching and lack of trained personnel. In this context, interviewees brought suggestions for enhancing Multiprofessional Residency programs. FINAL CONSIDERATIONS: This study evinced that MRH provided an institutional growth with consequent service quality improvements, which resulted in health care quality improvements. It stimulated a move from an Assistance Hospital to a Teaching Hospital and a growth of professional hospital staff through direct contact with residents. Contributed to service reorganization, enhancing team work and stimulating integral care practice. It favored Permanent Education process of clinical staff. Apart from this, RMS implementation found oder problems and it was necessary to face challenges and weaknesses arising from a lack of comprehension of RMS role, from a lack of knowledge of tutor and preceptor duties and resistance of clinical staff, especially in the implementation phase. In this research, some participants pointed out a lack of physical resources and materials, as well as a reduced professional staff, as factors that interfered with MRH organization. They also stressed a need for increasing hospital organization and communication with partner institution.